Дослідження геоелектричними методами інженерно-геологічного стану Південно-Західного Кривбасу. Частина 2. Результати застосування геоелектричних методів при обстеженні ділянок підтоплення - Пігулевський, П.Г.; Свистун, В.К.; Кирилюк, О.С. (Геоінформатика, 2016)
Проаналізовано можливості ефективного використання геоелектричних методів під час комплексного вивчення впливу техносфери на геологічне середовище Кривбасу для вирішення завдань екологічної безпеки. У другій частині статті наведено практичні приклади досліджень геоелектричними методами антропогенного впливу на геоекологічний стан міської агломерації в Кривбасі. За результатами комплексних геофізичних досліджень, що супроводжувалися геолого-гідрогеологічними спостереженнями та бурінням завіркових свердловин, отримано геолого-геофізичні розрізи та результативні карти зміни геоелектричних параметрів, які показують ступінь та інтенсивність водонасиченості горизонтів. Ці матеріали у сукупності з результатами попередніх досліджень дали змогу отримати карти та розрізи породних масивів, уточнити та конкретизувати деякі окремі особливості гідрогеологічного стану площі, яка досліджується, за чотирирічний період з 2008 по 2012 р. Анализируются возможности эффективного использования геоэлектрических методов с целью комплексного изучения влияния техносферы на геологическую среду Криворожского железорудного бассейна (Кривбасса) при решении задач экологической безопасности. Во второй части статьи приведены практические примеры исследований геоэлектрическими методами антропогенного влияния на геоэкологическое состояние городской агломерации в Кривбассе. По результатам комплексных геофизических исследований, которые сопровождались геолого-гидрогеологическими наблюдениями и бурением заверочных скважин, построены геофизические разрезы и результативные карты изменения геоэлектрических параметров, показывающие степень и интенсивность водонасыщенности горизонтов. Эти материалы в совокупности с результатами предыдущих исследований позволили получить карты и разрезы породных массивов, уточнить и конкретизировать отдельные особенности гидрогеологического состояния исследуемой площади за четырехлетний период с 2008 по 2012 г. The purpose of the paper is to conduct geophysical surveys to study engineering-geological conditions of the south-western part of Kryvbas in solving ecological safety problems.
Method. Analysis of the available petrophysical, engineering and hydrogeological information of the sedimentary cover rocks of the south-western part of Kryvbas. Selection of optimal parameters for the vertical electrical sounding (VES). Implementation of field research with the VES method of the natural electric field; and of the method of qualitative and quantitative interpretation to determine the changes of geoelectric parameters of the rock mass, associated with the space-time changes in the hydrogeological conditions of the geological environment of the four-year period from 2008 till 2012.
Results. We have done geological and geophysical sections based on the results of qualitative and quantitative interpretation of VES of natural electric field, which provid additional information about the structure and parameters of the aquifer system of the Neogene-Quaternary sediments. Based on these materials, together with the results of the previous studies, we have obtained, maps which clarify and specify the features of the hydrogeological condition of the studied area in three-dimensional performance, and for a four-year period from 2008 till 2012. In determining groundwater levels from the first surface of the aquifer according to VES, NEF and dowsing we identified filtration flows and their distribution over the area, as well as intensity and direction. The reliability of the geophysical investigations was proved by definition drilling, the information from the restricted network of the wells, and water level measurements in the wells.
The practical significance and conclusions. The suggested technology of research allows quick detection and mapping of the zones of flooding by geoelectrical methods for a complex study of the effect of the techno sphere on the geological environment of Kryvbas in solving problems of ecological safety.